Childhood Maltreatment, Automatic Negative Thoughts, and Resilience: The Protective Roles of Culture and Genes - Yu, Meihua (Journal of interpersonal violence, 2022)
Resilience, a psychological trait conceptualized as the ability to recover from setbacks, can be weakened by childhood maltreatment, which comprises childhood abuse and childhood neglect. The current study aimed to investigate whether childhood maltreatment could increase automatic negative thoughts (ANT), thus weakening resilience. Furthermore, as psychological characteristics are commonly subject to the moderating effects of cultural context and biology, the study also explored whether and how cultural and genetic factors separately interact with childhood maltreatment to predict resilience. In study 1, the participants comprised 237 American and 347 Chinese individuals; study 2 included 428 genotyped Chinese individuals. We combined regression, mediation, moderation, and machine learning methods to test the mediating effect of ANT on the link between childhood maltreatment and resilience as well as the moderating roles of culture and genetics. Study 1 found that both childhood abuse and childhood neglect increased ANT and thus weakened resilience. In addition, the ANT-mediating effects of childhood neglect were stronger in American than Chinese participants. In Study 2, using the leave-one-out approach, we constructed two separate prediction models based on 22 and 16 important single nucleotide polymorphisms (SNPs), and we found that the interaction between childhood abuse/neglect and polygenic scores based on important SNPs could predict ANT. The mediating effects of ANT on the relationship between childhood abuse/neglect and resilience were significant for participants with low polygenic scores but not for those with high polygenic scores. In conclusion, both the cultural environment and individual genetic makeup moderated the mediating effects of ANT on the association between childhood maltreatment and resilience. These findings indicated the roles of culture and genetics in protecting against the adverse effects of childhood maltreatment on resilience.